Women at Work: Unveiling the impact of FLFPR and adolescent fertility on India's economic landscape - Mahima Chandauriya; Pawan Kumar Sharma (National Geographical Journal of India, 2024)
This paper aims to understand the correlation between FLFPR, adolescent fertility rate and economic development of India between 2012 and 2022. Based on quantitative and secondary research data, this research analyses the effect of FLFPR, FGERSE and adolescent fertility rates on GDP per capita. Data imply that FLFPR has a positive relation with the GDP per capita proving that women play a mature role within the scheme of economic development. On the other hand, adolescent fertility rates are grossly inversely related to GDP per capita and thus should warrant policies supporting reproductive health outcomes. Moreover, the study shows that there is need to advocate for gender main stream education for the provision of sustainable economic for women and gender equality in India.